2020
DOI: 10.1186/s13256-020-02420-x
|View full text |Cite
|
Sign up to set email alerts
|

Giant paratesticular liposarcoma with lung metastases: a case report and review of the literature

Abstract: Background: Due to its rarity, little is known about the clinical presentations and responses to systemic chemotherapies in advanced and/or metastatic cases of paratesticular liposarcoma. Case presentation: Here, we report the case of a 75-year-old Japanese man with giant paratesticular liposarcoma. Imaging studies revealed a 26 cm tumor in his right scrotum and lung metastases at presentation. He underwent radical orchiectomy followed by systemic chemotherapies. Pathological findings of the resected primary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In comparison to dedifferentiated or well-differentiated liposarcoma, myxoid liposarcoma exhibits relative resistance to chemotherapy. The response rate of dedifferentiated liposarcoma to first-line chemotherapy, including doxorubicin alone (8%) or in combination with ifosfamide (17%), was notably lower, reaching only 25% [ 4 ]. The primary treatment for PTML involves surgical resection with wide margins, as achieved in this case through the high orchidectomy procedure [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to dedifferentiated or well-differentiated liposarcoma, myxoid liposarcoma exhibits relative resistance to chemotherapy. The response rate of dedifferentiated liposarcoma to first-line chemotherapy, including doxorubicin alone (8%) or in combination with ifosfamide (17%), was notably lower, reaching only 25% [ 4 ]. The primary treatment for PTML involves surgical resection with wide margins, as achieved in this case through the high orchidectomy procedure [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over half of PLPS patients have WDLPS with a favorable prognosis. WDLPS can recur with low metastatic rates ( 12 ). The main route of metastasis for this tumour is through the inguinal canal that extends to the peritoneal cavity, and rarely through the blood and lymphatic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Eribulin, an inhibitor of the growth of microtubules, is very effective in patients with advanced liposarcoma as a second-line therapy ( 30 ). In a case with massive parasternal liposarcoma that had metastasized to the lungs, gemcitabine combined with docetaxel therapy was reported to have controlled the cancer after one year ( 12 ). There is limited evidence for the effectiveness of chemotherapy for PLS, but we believe that chemotherapy would help improve survival in patients with advanced or distant metastases, in some studies, chemotherapy was suggested as a treatment for high grade LPS.…”
Section: Discussionmentioning
confidence: 99%
“…In a study that included 265 cases of PLS, adjuvant radiation therapy was found to have no statistical impact on recurrence-free survival (1). Although liposarcoma is less likely to develop distant metastases, chemotherapy may still be required to control the disease in inoperable and metastatic PLS (16). Jones et al found that dedifferentiated liposarcoma had a response rate of only 25% to first-line chemotherapy (17).…”
Section: Discussionmentioning
confidence: 99%
“…Takuro Noguchi et al. reported a giant paratesticular liposarcoma with pulmonary metastases that was well controlled after 1 year of gemcitabine combined with doxorubicin chemotherapy ( 16 ). Evidence for effective chemotherapy for PLS is limited, but we believe systemic chemotherapy may contribute to the survival of patients with advanced and distant metastases.…”
Section: Discussionmentioning
confidence: 99%